Investigation of the Supply Chain Management Effects on the Foreign Trade Development of Iran in the Context of Other Countries of Southwest Asia - Ramezani Galeshi, Morteza (ExcelingTech, 2019)
Foreign trade can present productivity increase in production and economy growth by using scale gain, developed technology, optimum allocation of source and supply chain management. Also, economic freedom influences many variables which one of the most important ones is foreign trade or level of exports and imports. In other word, influence of economic freedom and supply chain management on foreign trade process is very important. Therefore, it is necessary to surveys relationship between foreign trade, supply chain and economic freedom variables on countries of the region of Southwest Asia based on collected information in the period of 2001-2018. Model estimation results show Economic Freedom and economic growth has positive and statistically significant effect on foreign trade in Iran and selected countries. Also, the effect of Inflation rate on foreign trade is negative but not statistically significant. Finally it was concluded that by supply chain management especially in logistics and transportation system of the foreign trade, the efficiency increased significantly.